The discursive organization of research interviews - Grinsted, Annette (HERMES - Journal of Language and Communication in Business, 2001)
The article discusses two methods for assessing beliefs, values etc. and underlying factors, viz. structured and semi-structured interview. The application of semi-structured interviews is exemplified in connection with a study carried out by the author, emphasisíng especially the role of accounts for assessing factors underlying beliefs, judgments, etc.